Q:

A) 19 | B) 29 |

C) 39 | D) 49 |

Answer: C) 39

Explanation:

Explanation:

Let B's present age = x years. Then, A's present age = (x + 9) years.

(x + 9) + 10 = 2(x - 10)

=> x + 19 = 2x - 20

=> x =39.

Q:

A) 23 : 19 | B) 17 : 11 |

C) 27 : 20 | D) 34 : 23 |

2
268

Q:

A) 20 years | B) 18 years |

C) 24 years | D) 22 years |

4
437

Q:

A) 40, 44, 36 | B) 44, 40, 36 |

C) 34, 26, 30 | D) 30, 26, 34 |

1
354

1
315

Q:

A) 17 years | B) 16 years |

C) 15 years | D) 14 years |

1
419

0
341

Q:

A) 16,36,28 | B) 16,28,36 |

C) 20,35,45 | D) 12,21,27 |

9
617

3
435